Зовнішньоекономічна політика в системі управління потенціалом споживання ті заощадження секторів національної економіки - Фомішина, В.М. (Культура народов Причерноморья, 2014)
В статті обґрунтовано положення, що дієва державна зовнішньоекономічна політика
держави є необхідною умовою економічної стабілізації і передумовою зростання доходів, споживання
та заощадження. Визначена роль секторів національної економіки, залучених у споживчо-інвестиційні
процеси. Акцентовано, що з огляду на високу відкритість економіки України значний вплив на
споживчо-заощаджувальні процеси здійснюють цілі, складові та інструменти зовнішньоекономічної
політики. В статье обосновано положение, что действенная государственная внешнеэкономическая
политика государства является необходимым условием экономической стабилизации и предпосылкой
роста доходов, потребления и сбережения. Обоснована роль секторов национальной экономики,
вовлеченных в потребительско-инвестиционные процессы. Акцентировано, что с учетом высокой
открытости экономики Украины значительное влияние на потребительско-сберегательные процессы
процессы оказывают цели, составляющие и инструменты внешнеэкономической политики. In the article the proposition that effective government foreign policy is a necessary condition for
economic stabilization and a prerequisite for the growth of income, consumption and savings. Definitions, which
control the consumption and savings based on consideration of the sectoral structure of the economy and
implemented at different levels – the mega, macro, macro national economy. Regulator is an acting
supranational bodies and national institutional units which are parties to both of consumers – saving processes.
The role of the national economy sectors involved in consumer – Investment Paper processes. The attention
which is due to the high openness of the economy Ukraine a significant impact on consumer – saving processes
engaged objectives, components and tools of foreign policy. The statement that the greatest impact on final
consumption and saving has foreign policy and trade surplus is not always objective indicator of well–being of
the country, in terms of optimal consumption criterion is the policy of leveling the trade balance. It is shown that
in addition to foreign policy, the amount and dynamics of consumption and savings affect monetary policy,
customs policy, the policy of attracting foreign investment.